An Approach to Understanding Hadith on Polygamy: Maʿānī al-Ḥadīth - Kholil Syamsul (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Studies of hadith on polygamy have largely been dominated by textual and fiqh-centered approaches that position hadith as normative legitimization of polygamous practice, without adequately considering the historical, social, and ethical contexts that underlie them. Such approaches risk reducing the prophetic message of hadith and neglecting the principles of justice and humanity that constitute the core spirit of Islamic teachings. This study aims to analyze the hadiths of the Prophet Muhammad (peace be upon him) concerning polygamy using the Maʿānī al-Ḥadīth approach in order to uncover their substantive meanings, moral messages, and normative orientations within contemporary social contexts. This research employs a qualitative approach using library research methods. Primary data consist of hadiths on polygamy found in canonical hadith collections, supported by relevant Qur’anic verses. Secondary data include classical and contemporary hadith commentaries (sharḥ al-ḥadīth), scholarly works by classical and modern Muslim scholars, as well as articles from reputable academic journals published within the last three years. Data analysis is conducted through the Maʿānī al-Ḥadīth approach by considering historical contexts (asbāb al-wurūd), the social conditions of pre-Islamic Arabian society, and the normative objectives of hadith within the framework of maqāṣid al-sharī‘ah. The findings indicate that hadiths concerning polygamy were not intended as an ideal normative model, but rather as corrective and transitional social regulations. Justice emerges as the core message of polygamy-related hadiths, articulated through exceptionally high moral standards encompassing material, psychological, and emotional dimensions. Polygamy is thus positioned as a moral test and a prophetic trust fraught with ethical risks, rendering it inappropriate to promote as an ideal practice. This study underscores the importance of contextual, justice-oriented, and human-centered approaches to hadith interpretation that prioritize human welfare and ethical responsibility.